UTILIZATION OF COW DUNG AND RABBIT URINE FERTILIZER TO OPTIMIZE THE GROWTH OF LIBERICA COFFEE SEEDLINGS (Coffea liberica L.) - Rosniawaty, Santi; Abdul Halim luthfi; Intan Ratna Dewi Anjarsari; Mira Ariyanti; Rija Sudirja (Universitas Veteran Bangun Nusantara, 2025)
Liberica coffee (Coffea liberica L.) has the advantage of growing on marginal land and showing resistance to pests and diseases. To support optimal growth, Liberica coffee seedlings require appropriate growing media and nutrient sources. Cow manure and rabbit urine, as organic waste, are expected to provide sufficient nutrients. This study aimed to evaluate the effect of cow manure and rabbit urine on the growth of Liberica coffee seedlings. The experiment was conducted from February to June 2023 at the Ciparanje Experimental Garden, Faculty of Agriculture, Universitas Padjadjaran, using a randomized block design (RBD) with nine treatments and three replications. Treatments consisted of (A) soil + 2 g urea, (B) soil + 25% rabbit urine, (C) soil + 50% rabbit urine, (D) soil:cow manure (1:1) + 25% rabbit urine, (E) soil:cow manure (1:1) + 50% rabbit urine, (F) soil:cow manure (2:1) + 25% rabbit urine, (G) soil:cow manure (2:1) + 50% rabbit urine, (H) soil:cow manure (3:1) + 25% rabbit urine, and (I) soil:cow manure (3:1) + 50% rabbit urine. The application of cow manure and rabbit urine increased leaf area, root length, and chlorophyll index of Liberica coffee seedlings. The best growth was achieved with the combination of soil:cow manure (3:1) and 25% rabbit urine, which also increased the levels of total N, P2O5, and K2O in the seedlings. Keywords : coffee, liberica,nutrition content, organic, seedling